Quest for Female's Identity in Tiwari's Prashnaharuko Kārkhānā - Mishra, Indira Acharya; Rana, Luna (Dristikon: A Multidisciplinary Journal, 2021)
Sarita Tiwari (2015) in her collection of poems, Prashnaharuko Kārkhānā [Factory of Questions] protests the tradition of wearing ornaments and cosmetics by women. Likewise, she rejects the use of submissive symbols and metaphors that have been used by the creative writers to define women. She identifies them as ploys that patriarchy has invented to maintain the subordination and subjugation of women to men. She argues that these techniques mystify and blur women's identity, so she questions and challenges them. Thus, this article analyzes five poems from the anthology to examine how the poet protests the traditional norms and values of patriarchy that define women as secondary to men and search for female's identity through them. To examine the quest for female's identity in her poetry, this article takes theoretical support from feminist critics like Mary Daly, Kate Millet, Naomi Wolf and others. These critics believe that patriarchy uses different types of myths to maintain women's secondary position in the society. The article concludes that in the quest for female's identity independent of men, Tiwari protests the tradition and culture that emphasize women's beauty and their submissive roles in the society. Through their interrogating tone and syntax, the selected poems challenge patriarchal norms which have been imposed upon women to erase their identity. The study helps to understand how patriarchy manipulates the myths of religion and beauty to maintain males’ supremacy over females.